2019
DOI: 10.1002/admt.201900266
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Production of a Shelf‐Stable Living Material as a Biosensor Platform

Abstract: analyze biomarkers in human diseases, such as nitrogen oxides involved in inflammation response. [11] This organismbased type of sensor systems is referred to as whole-cell biosensors, since the sensing functionality and signal transduction require intact, living cells. The basic working principle of a whole-cell biosensor relies on an input, which activates a certain pathway in the cell leading to an output signal such as color, fluorescence, or luminescence that can be measured by the user. [12,13] Cells gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Additional techniques used for the fabrication of ELMs include wet spinning and roll-to-roll processes. 104,105 Both wet-spinning and roll-to-roll techniques are highly scalable. For wet spinning methods used in ELMs, polyvinyl alcohol (PVA) microfibers containing dispersed Micrococcus luteus or Nitrobacter winogradskyi bacteria were used for gold sequestration and nitrate bioremediation, respectively.…”
Section: Processing Techniques For the Manufacturing Of Stimuli-responsive Elmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional techniques used for the fabrication of ELMs include wet spinning and roll-to-roll processes. 104,105 Both wet-spinning and roll-to-roll techniques are highly scalable. For wet spinning methods used in ELMs, polyvinyl alcohol (PVA) microfibers containing dispersed Micrococcus luteus or Nitrobacter winogradskyi bacteria were used for gold sequestration and nitrate bioremediation, respectively.…”
Section: Processing Techniques For the Manufacturing Of Stimuli-responsive Elmsmentioning
confidence: 99%
“…It was observed that cells retained functionality during this process as they were capable of generating a fluorescence signal after IPTG sensing. 105 In summary, the combination of synthetic biology and materials science offers new methods to develop stimuli-responsive ELMs with well-defined functions. High specificity to a variety of molecules can be programmed into cells to produce composites that sense, respond, and modify the physical or chemical properties of the material itself or the surrounding environment.…”
Section: Processing Techniques For the Manufacturing Of Stimuli-responsive Elmsmentioning
confidence: 99%
“…[1][2][3] Examples of ELMs include biofilters to sequester metals [4] or viruses, [5] bacterial hydrogels for biosensing, [6] shape-morphing composites, [7] self-healing adhesives, [8] photosynthetic biogarments [9] or self-regulated drug delivery devices. [10] A common feature in these constructs is the encapsulation of the organisms within matrices including natural polymers like agarose, [11,12] alginate, [13] and dextran, [14] synthetic polymers like polyvinyl alcohol [15] and Pluronic, [16,17] or inorganic matrices like porous silica. [18] Alternatively, proteinaceous [19] or cellulose [6] matrices produced by the organisms themselves, as in a biofilm, can serve as encapsulating networks.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, a portable system for spore-based whole-cell biosensing of arsenite and zinc in a centrifugal compact disk microfluidic platform was functionally stable for 1 year under elevated temperature and a variety of humidity/drought conditions 85 . A living material polymer device containing B. subtilis spores encapsulated in a PVA matrix for continuous sensing of small-molecule analytes could be stored for extended time periods at room temperature without compromising sensor function 86 . Incorporating hydrogel encapsulation with a paper-based device, Weaver et al 87 first developed a whole-cell yeast paper-based biosensor device to yield a biologically based paper analytical device (BioPAD), which could be stored at 4 °C and 37 °C and remain viable for at least 6 months and 56 days respectively.…”
Section: Biosensingmentioning
confidence: 99%